2023
DOI: 10.1111/bjh.18758
|View full text |Cite
|
Sign up to set email alerts
|

Combining MYD88 L265P mutation detection and clonality determination on CSF cellular and cell‐free DNA improves diagnosis of primary CNS lymphoma

Abstract: Summary Diagnosis of primary central nervous system lymphoma (PCNSL) is challenging, and although brain biopsy remains the gold standard, cerebrospinal fluid (CSF) constitutes a less invasive source of lymphomatous biomarkers. In a retrospective cohort of 54 PCNSL cases tested at diagnosis or relapse, we evaluated the contribution of immunoglobulin heavy chain (IGH) gene clonality and MYD88 L265P detection on both CSF cell pellets and supernatants, in comparison with cytology, flow cytometry, interleukin (IL)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[ 12 , 18 ] Recent research underscores the utility of CSF-based diagnostics, particularly related to the myeloid differentiation primary response gene 88 (MYD88) L265P mutation. [ 1 ] For instance, Yamaguchi et al . reported a novel rapid genotyping system, GeneSoC, which uses real-time polymerase chain reaction to detect the MYD88 mutation effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 , 18 ] Recent research underscores the utility of CSF-based diagnostics, particularly related to the myeloid differentiation primary response gene 88 (MYD88) L265P mutation. [ 1 ] For instance, Yamaguchi et al . reported a novel rapid genotyping system, GeneSoC, which uses real-time polymerase chain reaction to detect the MYD88 mutation effectively.…”
Section: Discussionmentioning
confidence: 99%
“…[12,18] Recent research underscores the utility of CSFbased diagnostics, particularly related to the myeloid differentiation primary response gene 88 (MYD88) L265P mutation. [1] For instance, Yamaguchi et al reported a novel rapid genotyping system, GeneSoC, which uses real-time polymerase chain reaction to detect the MYD88 mutation effectively. [19] is innovation reinforces the evolving landscape of PCNSL diagnostics, offering potential advancements for both intra-and preoperative diagnosis through CSF analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular testing for Myd88 and IgH mutations and cytokine analysis for IL-10 may support a diagnosis of CNS lymphoma in the absence of histologic and cytologic confirmation. 31,32 Ultimately, there are inevitable situations where a biopsy cannot be safely performed and CSF analysis is unrevealing. In these situations, we will arrive at a presumed diagnosis together in multidisciplinary discussion with radiology, neurosurgery, and oncology.…”
Section: When Tissue Diagnosis Cannot Be Performedmentioning
confidence: 99%